Global numerical analysis of elasto-plastic frames 1 - Gáspár, Zsolt; Nédli, Péter (Computer Assisted Methods in Engineering and Science, 1998)
We discuss a global, iteration-free numerical scheme (based on the Piecewise Linear algorithm), with special respect to the computation of elasto-plastic frames. The plastic deformations are concentrated in plastic hinges which may appear at both ends of the bars, while the inner parts of the bars can have only elastic deformations but without limation on their magnitude. Our method is tested on a classical example and the results show very good match with those known from the literature. We discuss advantages and disadvantages and point out other, related applications.